Characterization of pulmonary vein reconnection post Cryoballoon ablation - Shivang Shah; Wenjie Xu; Evan Adelstein; Andrew Voigt; Samir Saba; Sandeep Jain (Indian Pacing and Electrophysiology Journal, 2019)
Background: The Arctic Front Cryoballoon System is a technology in which substrate alterations in patients with atrial fibrillation (AF) recurrence have not been well characterized. In this study, we evaluated sites of pulmonary vein (PV) reconnections and the accuracy of the Achieve™ circular mapping catheter in detecting these reconnections after cryoablation. Methods: This study included 15 patients undergoing redo AF ablation after a prior single cryoablation procedure. PV reconnection sites were determined by measuring PV signals and high output pacing from 4 vectors of the Achieve catheter. The results were compared with a roving mapping catheter guided by rotational intracardiac echocardiography (ICE) in the left atrium. Results: All patients had PV reconnections (2.1 ± 0.8 veins/patient). The left superior PV was most commonly reconnected (n = 11), whereas the right inferior PV was least likely (n = 3). Both carinas (left: n = 11; right: n = 7) and left atrial appendage ridge (n = 11) were also frequently reconnected. Mapping with the Achieve catheter showed a positive predictive value (PPV) 100% and negative predictive value (NPV) 96% when compared with ICE guided mapping. In 2 patients, right superior PV reconnection was not identified by the Achieve. Conclusion: During redo AF ablation after index cryoablation, multiple PVs are usually reconnected, with both carinas and left atrial appendage ridge being common sites of reconnection. The Achieve mapping catheter was able to identify reconnection with high positive and negative predictive values. Key words: Achieve™, Cryoballoon, Ablation, Atrial Fibrillation, Pulmonary veins reconnections